Abundance and characteristics of microplastics in the northern coastal waters of Surabaya, Indonesia. (May 2019) - Cordova, Muhammad Reza; Purwiyanto, Anna Ida Sunaryo; Suteja, Yulianto
Abstract: Microplastic distribution in waters gained increasing attention because of the discovery of microplastics in edible marine organisms. Microplastic size is small, and hence, it tends to float in the water column, thereby making it easy to enter and accumulate in the marine organism. Microplastic abundance is highly associated with the population density. The North Coast of Surabaya is the main area for community activities in East Java; therefore, it is highly vulnerable to receive microplastic input from the mainland. This study aimed to analyze the abundance, distribution, and characteristics of microplastics in the northern coastal waters of Surabaya. The study was conducted in March 2017. The results showed that the highest and lowest microplastic abundances were found in Lamong Bay. The microplastic characteristics in all stations showed that foam was the dominant form and polystyrene was the dominant type, with sizes of 500–1000 μm and 300–500 μm. Highlights: The highest abundance of microplastics obtained in the closest area to the land The observed floating microplastics dominated from secondary sources. The domination of PS shows the sources from Surabaya anthropogenic activities. Large-sized found is an indication that microplastics degraded in a short time.